Comparative analysis of trade and finance in emerging economies - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics ;, 2023)
This volume of the International Symposia in Economic Theory and Econometrics explores the latest economic and financial developments in Africa and Asia. Chapters cover a range of topics such as: the relationship between good stewardship, agency costs, and performance of South African firms; stock market dynamics in Thailand, including risk & mutual fund clustering and zero-investment portfolios strategies; and a special focus on financial markets in Indonesia such as fundamental indexing with Markowitz mean variance portfolios, a financial performance analysis of highway companies before and during the Covid-19 pandemic, and a credit risk scoring model for consumer financing. Comparative Analysis of Trade and Finance in Emerging Economies also addresses the issue of whether the West African Monetary Zone can form a Currency Union, and, examines the impact of non-tariff measures of China on the export of agricultural products of Laos. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as stock markets and the effects of public policy. Together, ISETE 31, is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.